Analysis of the Implementation of the Construction Safety Management System (SMKK) on the Cisempur-Budiwangi Road Reconstruction Activity, Cibalong District Tasikmalaya Regency - Nuruzzaman, Wildan (Jurnal Improsci, 2023)
The construction service industry is an industrial sector with a high risk of work accidents. For this reason, implementing the Construction Safety Management System (SMKK) is expected to reduce the number of work accidents. Many Road Reconstruction construction projects are carried out without implementing the Construction Safety Management System (SMKK) following the rules referring to PUPR Minister Regulation Number 10 of 2021 concerning Construction Safety Management System Guidelines. This study aims to determine the implementation of the Construction Safety Management System (SMKK) on Cisempur – Budiwangi Road Reconstruction Activities, Cibalong District, Tasikmalaya Regency. The research was conducted in several places in the Budiwangi Road Reconstruction project, Cibalong District, Tasikmalaya Regency. This research is qualitative descriptive, with data obtained by observation, conducting interviews, and filling out checklists. The results of the study: 1). The level of implementation of the Construction Safety Management System (SMKK) with a percentage value of appropriate application of 67.44% and findings of nonconformity of 32.56% (Minor Category). 2). The factor causing the non-fulfillment of applications is the absence of processing documents and special formats for changes in the field that impact K3. 3) Response and improvement actions that can be taken are to create special procedures and formats related to changes that have implications for K3.